2015
DOI: 10.1093/jme/tjv197
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Dynamics, Parity Rate, and Composition ofCulicoides(Diptera: Ceratopogonidae) Occurring in the Vicinity of Wild and Domestic Ruminants in the Czech Republic

Abstract: In the light of the emergence of bluetongue and Schmallenberg viruses in northern and central Europe, an extensive entomological survey within the framework of a bluetongue control program was undertaken from 2008 to 2013 in the Czech Republic to investigate Culicoides biting midges (Diptera: Ceratopogonidae) collected in close proximity of domestic livestock and semiwild ruminants. Insects were sampled using CDC black-light suction traps placed overnight near ruminants in farms or in forest game preserves to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Czech Republic (Radrova et al 2015) An extensive survey was done between 2008 and 2013 at 34 sampling sites using CDC black-light suction traps that were placed overnight near ruminants in farms or in forest game preserves. The…”
Section: Eastern Europementioning
confidence: 99%
“…Czech Republic (Radrova et al 2015) An extensive survey was done between 2008 and 2013 at 34 sampling sites using CDC black-light suction traps that were placed overnight near ruminants in farms or in forest game preserves. The…”
Section: Eastern Europementioning
confidence: 99%
“…The role of Culicoides as vector species in wildlife has been limitedly investigated in the Palearctic region, excepted in relation to avian parasites transmission in wild bird populations [5]. In Europe, entomological studies have been carried out in both farms and game preserves in Spain [6] and in the Czech Republic [7]. In Spain, the species composition seems more influenced by the climate (dominance of Culicoides imicola under the southern Mediterranean climate, and of morphologically close species Culicoides obsoletus s.l.…”
Section: Introductionmentioning
confidence: 99%
“…In the Czech Republic, species belonging to the Avaritia and, at a much lesser extent, to the Culicoides subgenera were dominant in farms (~97% of the collected Culicoides ) and abundant in game preserves (~64%). Game preserves were associated with forest species such as Culicoides pallidicornis (~19%), Culicoides furcillatus (~3%), and Culicoides festivipennis (2%), often rare in farms [7]. These studies demonstrated that, under Mediterranean, oceanic, or wet continental climates, several Culicoides species, recognized as probable BTV vectors and belonging to the Avaritia and Culicoides subgenera, could be abundant in both farms and game preserves [6,7], where they are able to feed on wild ruminants [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to this regulation, a vector-free period is defined as the total absence of C. imicola, and less than five parous females of any other observed Culicoides vector species collected in light traps [23]. Monitoring of the parous rates in field populations contributes to an understanding of adult survival rates [24] and the voltinism of vector species [25,26].…”
Section: Introductionmentioning
confidence: 99%